Understanding psychopathy: the biopsychosocial perspective - Thomson, Nicholas D. (New frontiers in forensic psychology, 2019)
Psychopathy and the biopsychosocial model -- History and assessment of psychopathy -- Psychopathy and violent crime -- Genetics and the environment -- Biological factors -- Psychological factors -- Social factors -- The biopsychosocial model of psychopathy.